2021
DOI: 10.3389/fcell.2020.620459
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Reactive Müller Glia Gene Expression After Light Damage and microRNA-Depleted Müller Glia—Focus on microRNAs

Abstract: Müller glia (MG) are the predominant glia in the neural retina and become reactive after injury or in disease. microRNAs (miRNAs) are translational repressors that regulate a variety of processes during development and are required for MG function. However, no data is available about the MG miRNAs in reactive gliosis. Therefore, in this study, we aimed to profile miRNAs and mRNAs in reactive MG 7 days after light damage. Light damage was performed for 8 h at 10,000 lux; this leads to rapid neuronal loss and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 123 publications
1
21
0
Order By: Relevance
“…We confirmed that vascular permeability in IR retinas was also significantly decreased by 3 days of treatment, to a similar extent of that obtained after 7 days of treatment (data not shown). The mRNA examined included Tnfa, Il1b, Ptgs2, and Nos2, which are all considered markers of M1 microglial activation [ 59 , 60 ]; Cd68, which is considered a marker of microglia phagocyte phenotype [ 54 , 56 ]; Cyba and Cybb, corresponding to the NADPH oxidase complex members P22-pox and Gp91-phox, respectively; Lcn2 and Serpina3n, which are markers of reactive astrogliosis [ 61 ] and are greatly increased in the rat retinal IR injury model [ 34 ]; Arg1 (Arginase-1), Cd200r1 (CD200 receptor), Tgm2 (transglutaminase-2), and Mrc1 (CD206), which are all considered M2 markers [ 62 64 ]. Tnfa, Il1b, and Ptgs2 (Cox2) mRNAs were all significantly upregulated in IR injured retinas relative to Sham retinas, and all these inducements were significantly diminished by minocycline treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that vascular permeability in IR retinas was also significantly decreased by 3 days of treatment, to a similar extent of that obtained after 7 days of treatment (data not shown). The mRNA examined included Tnfa, Il1b, Ptgs2, and Nos2, which are all considered markers of M1 microglial activation [ 59 , 60 ]; Cd68, which is considered a marker of microglia phagocyte phenotype [ 54 , 56 ]; Cyba and Cybb, corresponding to the NADPH oxidase complex members P22-pox and Gp91-phox, respectively; Lcn2 and Serpina3n, which are markers of reactive astrogliosis [ 61 ] and are greatly increased in the rat retinal IR injury model [ 34 ]; Arg1 (Arginase-1), Cd200r1 (CD200 receptor), Tgm2 (transglutaminase-2), and Mrc1 (CD206), which are all considered M2 markers [ 62 64 ]. Tnfa, Il1b, and Ptgs2 (Cox2) mRNAs were all significantly upregulated in IR injured retinas relative to Sham retinas, and all these inducements were significantly diminished by minocycline treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, this may not have been due to a direct effect of minocycline on microglia. Lcn2 and Serpina3n were among the most highly upregulated mRNAs in reactive astrocytes following experimental stroke in mice [ 90 ], were both upregulated in Müller cells undergoing astrogliosis [ 62 , 91 , 92 ], and were recently identified as being highly upregulated in endothelial cells in a mouse experimental autoimmune uveitis model [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…But they are not the most sensitive ones in regarding inflammation. MiR-124, normally localizing to both INL and OLM of the retina, redistributes from neurons to MG with increased expression under photo-oxidative damage, targeting Ccl2 for retinal inflammation regulation ( Chu-Tan et al, 2018 ; Kang et al, 2020 ), suggesting its role behind the retinal inflammatory responses. The inflammation-related genes Fgf2, Mt2 and Ccl2 are regulated by MG miRNAs and predominantly by members of the let-7 family.…”
Section: Microrna Regulation and The Mgmentioning
confidence: 99%
“…In addition to regulating inflammation, miRNA profiling studies combined with broad blocking of miRNA function (e.g. Dicer knockout) are revealing the potential importance of many miRNAs in regulating neuronal regeneration in the zebrafish retina [11] and in reactive gliosis and understanding the mechanisms that prevent Müller glia reprogramming and neuronal regeneration in the mammalian retina [78]. Studies like these are bringing miRNA research to the forefront and showing the complexities of understanding pathways that govern neuronal regeneration.…”
Section: Discussionmentioning
confidence: 99%